Nowe technologie w pracy nauczyciela edukacji wczesnoszkolnej. Raport z badań - Iwanicka , Agnieszka (Studia Edukacyjne, 2019)
The new core curriculum for general education introduced in September 2017 (Journal of Laws 2017, item 356) introduced changes taking into account the use of new technologies in early school education. From now on, the school is to better prepare students for the requirements of a digital society, including a creative use of media. This requires the teacher’s readiness to introduce the media into the educational process, commitment to and efficient use of the digital media in individual education. I was wondering about the attitude of early school education teachers to using new technologies in lessons (especially in the context of the new curriculum). Moreover, I wanted to see if teachers show commitment to developing their own digital skills. Such an attitude would be justified: the high digital competences of teachers not only help the proper implementation of the core curriculum in grades 0-3, but also help in career promotion and prepare children for efficient functioning in a digital society. To answer the above questions, I carried out my own diagnostic survey on a group of 460 early school education teachers (N = 460), using a questionnaire. Teachers indicated a diverse attitude to both the changes introduced in the core curriculum and the use of digital media in education. They mainly point to their own digital incompetence in the use of new technologies in early school education lessons. New media are most often used in lessons by teachers older in terms of age and work experience; we can associate it with teachers’ professional promotion, which is connected with the requirement of using multimedia in the learning process as defined by the legislator. Teachers do not rate their digital skills too highly yet at the same time show interest in courses, trainings and workshops organized by the school, thanks to which they can improve their skills in this area. They also recognize that a digitally competent teacher is the answer to the needs of a new, modern school.